La influencia de Ramon Llull en el entorno del Cancionero de Juan Alfonso de Baena - Diaz Marcilla, Francisco Jose (2015)
Summary: The purpose of this study is, on the one hand, to shed light on the strictly historical aspects of the subject; to which end it will oﬀer a deeper analysis of the mediaeval texts and documents that help to understand the protagonists of Llullism in this Andalusian mould, within the context in which they lived. On the other hand, from a philosophical point of view, there is need for better knowledge of the ideas that provide the essential structure of this chansonnier, this collection of verse. Indeed it is perhaps here that it may be seen more clearly how Llullian thought is related to a lay philosophical current that favours a reasoned Christianity over other approaches, closer to the ecclesiastical sector, such as the “contemptus mundi”, asceticism or the sacerdotal way.